Interfacer: um método para especificação de interfaces para internet do futuro - Pereira Júnior, João Eurípedes (2019)
This thesis investigates how network management interfaces with enriched communication semantics can be specified and implemented. The motivation for this reseach came from the network testbed MTE/ETArch, whose objective was to investigate a semantic approximation between layers of the ISO model to improve the QoS/QoE based on comprehension of the needs of communicating entities and network adaptation to meet them. Starting from the point that the OWL ontology was not designed for strong semantics specifications, it reseaches which types of ontology can help to improve the semantic level of network management interfaces and which software engineering tools can help automate the development of these interfaces. In order to materialize this intention, first, it establishes a link between the activities of modeling and architecting networks relating traditional networks with Future Internet research initiatives and with recent trends of network softwarization. Second, it investigates how to employ the foundation ontology UFO, designed to deal with real-world semantics, in this testbed network. Third, we specify a domain ontology using OntoUML to represent a semantically-enriched management interface for the MTE/ETArch environment. Finally, this ontology is used to demonstrate how the integration of modeling and development infrastructures can help interfaces to readly reflect any changes in the ontology. The main contribution of this work is to propose the increase of the semantic accuracy of management interfaces to alleviate the load of semantic evaluation over the network managers. It is noticed that the way to achieve network management interfaces with a more refined semantics goes through ontologies. Nevertheless, it suspects that it will be necessary to use other formal semantic theories to establish a semantic framework, and much remains to be investigated in this regard.